A Computational Infrastructure Model for Research on Computer Vision - Nazaré Júnior, Antonio; Rodrigues, Marco; Melo, Victor; Correia, Arthur; Gonçalves, Gabriel; Nogueira, Keiller; Caetano, Carlos; Ferreira Júnior, Edemir; dos Santos, Jeferson; Schwartz, William (Anais do Brazilian e-Science Workshop (BreSci); 2015: Anais do IX Brazilian e-Science Workshop, 2015)
With the advances on science, a powerful computational infrastructure is desirable to increase the performance of experiments. The same holds true for research on the Computer Vision field, which deals with large amounts of data and also requires intensive computation. Nevertheless, the administration of a computational infrastructure involves many tasks, such as system configuration, preventive maintenance and storage management, which becomes very challenging for many research groups. With that in mind, this work proposes an infrastructure model to assist researchers with focus on Computer Vision. We conducted a series of tests to evaluate the performance of our model and the processing power of our infrastructure.